Methods of acute biological assays in guinea-pigs for the study of toxicity and innocuity of drugs and chemicals - Gui Mi Ko; Adela Rosenkranz; Clélia Rejane Antonio Bertoncini; Neide Hyppolito Jurkiewicz; Mirian Ghiraldini Franco; Aron Jurkiewicz (Universidade de São Paulo, 2010)
In this study, 602 samples were tested by the following assays performed at the animal facilities (Cedeme) of the Federal University of São Paulo (UNIFESP): 385 for dermal irritability, 90 for ocular irritability (discontinued in 1995), 31 for systemic toxicity by injection, 26 for oral acute toxicity, 15 for toxicity by intracutaneous injection, 15 for skin sensitization, 15 for toxicity of serum and vaccines for human use, 14 for toxicity by intramuscular implantation, 7 for pyrogens, 2 for acute dermal toxicity, and 2 for irritation of mucous membrane. The following agents were tested: cosmetics and related substances (42.0%), chemicals used in industry (32.9%), plastics, rubber, and other polymers (15.9%), agrotoxics (4.0%), medicines (2.7%), and vaccines (2.5%). In the present description, emphasis was given to tests of dermal irritability and sensitization. This work was conducted entirely in animal facilities, according to our general belief that animal facilities at universities, while considering ethic principles and sanitary, genetic, nutritional, and pathophysiological controls, also require laboratories specialized in areas such as transgenics, cryopreservation, ambiental physiology, functional genomics, alternative models, and mainly activities and research on methods in toxicology, as focused in this study. Descrevemos os testes usados em ensaios biológicos de curta duração para estudo de toxicidade e inocuidade de cosméticos, fármacos e outras substâncias químicas, feitos no Biotério Central/Cedeme da Unifesp, de 1986 a 2000. Testamos 602 amostras nos seguintes ensaios: 385 de irritação cutânea, 90 de irritação ocular (até 1995), 31 de toxicidade sistêmica por injeção, 26 de toxicidade oral aguda, 15 de toxicidade por aplicação intracutânea, 15 de sensibilização da pele, 15 de toxicidade de soros e vacinas de uso humano, 14 de toxicidade por implantação intramuscular, 7 de pirogênio, 2 de toxicidade dérmica aguda e 2 de irritação da mucosa. Os agentes testados foram: cosméticos e suas matérias-primas (42,0%), substâncias químicas industriais (32,9%), plásticos, borrachas e outros polímeros (15,9%), defensivos agrícolas (4,0%), medicamentos (2,7%) e vacinas (2,5%). Aqui daremos ênfase aos ensaios de irritação e sensibilização cutânea. Este trabalho foi feito inteiramente em biotério, em consonância com a idéia de que os biotérios em universidades, sem deixar de considerar os princípios éticos pertinentes e sem desconsiderar a presença de laboratórios para controles sanitário, genético, nutricional e fisiopatológico, devem ter também laboratórios para pesquisa em transgênicos, criopreservação, fisiologia ambiental, genômica funcional, modelos alternativos e fundamentalmente toxicologia, entre outros.